Proton conductivity properties of novel tin(II) phosphonates - Cañamero-Cebrián, Fernando; Cabeza-Díaz, Aurelio; Vílchez-Cózar, Álvaro; Bazaga-García, Montse; Ramírez-Losilla, Enrique; Olivera-Pastor, Pascual; Pérez-Colodrero, Rosario Mercedes (My University, 2024)
Metal phosphonates (MPs), a subclass of coordination polymers, may exhibit acidic groups such as P-OH, SO3H, COOH, N+-H, etc. Combining these features with interesting metals make them highly appealing in the field of fuel cells and electrolysers as potential proton conductors [1,2]. In this communication, we report the synthesis, characterization, and proton conduction properties of a series of Sn2+ hydroxyphosphonoacetates with a different water content, obtained at RT, 80 ºC and 150 ºC. The anhydrous 150 ºC-synthesized phase crystallizes in the monoclinic system, s.g. P 21/n. Its crystal structure, solved ab initio from laboratory powder X-ray diffraction data, is composed of distorted pyramidal Sn2+ polyhedra connected through the oxygen atoms from the phosphonate, hydroxyl, and carboxylic groups of the ligand (Figure 1). The proton conductivity was found to increase with the water content. A study of the possible effect of hydrated amorphous phases on proton conductivity is underway.
Keywords: Cristalografía - Congresos; X-ray diffraction; Proton conductivity; Metal phosphonates; Coordination polymers; Tin(II); Crystal structure